2018
DOI: 10.3390/soc8040125
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Islam: The Hijab and the American Workplace

Abstract: The United States Constitution allows individuals to practice any religion they choose. However, the austerity of this right is tested when an individual's belief is publicly displayed. For Muslim women wearing the hijab, or headscarf, the intersection between private religious practice and its social expression is explored on a daily basis. To fully understand the manifestation of public religious expression, this paper examines a series of interviews with 35 hijab-wearing Muslim women living in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…It acted as an emblem of their Otherness , reinforcing the binary of ‘us’ and ‘them’ and functioned as a “racializing agent” (Selod, 2018, p. 79). This is consistent with studies demonstrating that women who wear a hijab are more likely to face discrimination in the workplace (Aziz, 2012; Koura, 2018; Tariq & Syed, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…It acted as an emblem of their Otherness , reinforcing the binary of ‘us’ and ‘them’ and functioned as a “racializing agent” (Selod, 2018, p. 79). This is consistent with studies demonstrating that women who wear a hijab are more likely to face discrimination in the workplace (Aziz, 2012; Koura, 2018; Tariq & Syed, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Muslim women also experience mental health problems caused by religious and gender discrimination. According to Koura (2018), this discrimination is caused by stereotyping and stigmatization by non-Muslims after the 9/11 incident. These issues lead to problems related to mental health problems, such as stress, depression, fear and phobia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Muslim minority countries, such as the United States and Europe, wearing the veil (hijab) is among the factors giving rise to discrimination against Muslim career women. Koura (2017Koura ( & 2018 showed that there were several cases in the United States involving Muslim women who were fired for wearing a veil (hijab) at their workplace. Besides that, Weichselbaumer (2020) found that wearing the veil (hijab) had a negative impact on the lives of Muslim women.…”
Section: Findings and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…On a similar level, hijabisstereotyped with a host of negative attitudesare documented as particularly and increasingly subject to various forms of Islamophobic discrimination in the work-sphere (Koura 2018;Mahmud and Swami 2010). While emerging scholarship here is rarely in-depth, it points to the lack of research on discrimination based on religious attire and presents 'direct evidence for both formal and interpersonal discrimination and low expectations of receiving job offers among Hijabis' (Ghumman and Ryan 2013: 692;Abdelhadi 2019;Ghumman and Jackson 2010;Strabac et al 2016).…”
Section: Scholarship Around the Islamic Hijabimentioning
confidence: 99%